3

I have the following code:

\documentclass[a4paper,11pt]{book}
\usepackage[T1]{fontenc}
\usepackage[utf8]{inputenc}
\usepackage{lmodern}
\usepackage{classicthesis}
\usepackage{hyperref}
\usepackage{graphicx}
\usepackage[english]{babel}
\usepackage{amsmath,mathtools}
\usepackage{amsfonts}
\usepackage{color}
\usepackage{url}
\usepackage{enumitem}
\usepackage{multicol}
\usepackage{tabu}
\usepackage{amsthm}
\usepackage{fourier-orns}
\usepackage{framed}
\usepackage{tcolorbox}
\usepackage[toc,page]{appendix}
\usepackage[all]{xy}

\begin{document}

\begin{enumerate}
\item For the function $y=x,$ find the derivative, $y'.$
\[y'=\lim_{h\to 0}\frac{(x+h)-x}{h}=\lim_{h\to 0}\frac{h}{h}=\lim_{h\to 0}1=1.\]
\item For the function $y=x^2,$ find the derivative, $y'.$
\begin{align*}
y'=\lim_{h\to 0}\frac{(x+h)^2-x^2}{h}&=\lim_{h\to 0}\frac{x^2+2xh+h^2-x^2}{h}\\
&=\lim_{h\to 0}\frac{2xh+h^2}{h}=\lim_{h\to 0}(2x+h)=2x.
\end{align*}
    \begin{center}
        \begin{framed}
For the next two examples, we will use the angle sum formula for sine, which is
\[\sin(\alpha+\beta)=\sin\alpha\cos\beta+\cos\alpha\sin\beta.\]
        \end{framed}
    \end{center}
\item For the function $y=\sin x,$ find the derivative, $y'.$
\begin{align*}
y'=\lim_{h\to 0}\frac{\sin (x+h)-\sin x}{h}&=\lim_{h\to 0}\frac{\sin x\cos h+\cos x\sin h-\sin x}{h}\\
&=\lim_{h\to 0}\frac{\sin x(\cos h-1)+\cos x\sin h}{h}\\
&=\left[\lim_{h\to 0}(\sin x)\left(\frac{\cos h-1}{h}\right)\right]\left[\lim_{h\to 0}(\cos x)\left(\frac{\sin h}{h}\right)\right]\\
&=(\sin x)\cdot 0+(\cos x)\cdot 1\\
&=\cos x,
\end{align*}
where we have used $\displaystyle\lim_{h\to 0}\frac{\sin h}{h}=1$ and $\displaystyle\lim_{h\to 0}\frac{\cos h-1}{h}=0$ from section (1.3).
\item Find $\dfrac{d}{dx}\tan x.$
\begin{align*}
\dfrac{d}{dx}\tan x=\displaystyle\lim_{h\to 0}\dfrac{\tan(x+h)-\tan x}{h}&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin(x+h)}{h\cos(x+h)}-\dfrac{\sin x}{h\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin(x+h)\cos x-\cos(x+h)\sin x}{h\cos(x+h)\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin[(x+h)-x]}{h\cos(x+h)\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left[\left(\dfrac{\sin h}{h}\right)\left(\dfrac{1}{\cos(x+h)\cos x}\right)\right]\\
&=\dfrac{1}{\cos^2(x)}=\sec^2 x.
\end{align*}
\end{enumerate}

\end{document}

And I keep getting the error "Something's wrong--perhaps a missing \item"

How to fix this?

7
  • 2
    The culprit is the center environment. Comment it out and the error is gone. Jul 30 '15 at 17:54
  • anyway to still center text there? Jul 30 '15 at 17:55
  • Also when framing text, the frame seems to be off center... i.e. too much space on the left Jul 30 '15 at 17:56
  • @GonzaloMedina how were you able to format my code? The {} in the GUI editor only formatted the first line : ( Jul 30 '15 at 18:07
  • 1
    I highlighted the code and used Ctrl+k. Jul 30 '15 at 18:14
4

You need \leavevmode before the framed environment; however, I'd like to suggest you another approach using the tcolorbox package (which you are already loading). Below a comparative example with the original framed and then with a tcolorbox of defined width (a \makebox was used to center the box with respect to the \textwidth):

\documentclass[a4paper,11pt]{book}
\usepackage[T1]{fontenc}
\usepackage[utf8]{inputenc}
\usepackage{lmodern}
\usepackage{classicthesis}
\usepackage{hyperref}
\usepackage{graphicx}
\usepackage[english]{babel}
\usepackage{amsmath,mathtools}
\usepackage{amsfonts}
\usepackage{color}
\usepackage{url}
\usepackage{enumitem}
\usepackage{multicol}
\usepackage{tabu}
\usepackage{amsthm}
\usepackage{fourier-orns}
\usepackage{framed}
\usepackage[many]{tcolorbox}
\usepackage[toc,page]{appendix}
\usepackage[all]{xy}
\usepackage[margin=2cm,showframe]{geometry}

\begin{document}

\begin{enumerate}
\item For the function $y=x,$ find the derivative, $y'.$
\[y'=\lim_{h\to 0}\frac{(x+h)-x}{h}=\lim_{h\to 0}\frac{h}{h}=\lim_{h\to 0}1=1.\]
\item For the function $y=x^2,$ find the derivative, $y'.$
\begin{align*}
y'=\lim_{h\to 0}\frac{(x+h)^2-x^2}{h}&=\lim_{h\to 0}\frac{x^2+2xh+h^2-x^2}{h}\\
&=\lim_{h\to 0}\frac{2xh+h^2}{h}=\lim_{h\to 0}(2x+h)=2x.
\end{align*}
      \begin{center}\leavevmode
        \begin{framed}
For the next two examples, we will use the angle sum formula for sine, which is
\[\sin(\alpha+\beta)=\sin\alpha\cos\beta+\cos\alpha\sin\beta.\]
        \end{framed}
        \end{center}
        \makebox[\linewidth]{%
          \begin{tcolorbox}[arc=0pt,outer arc=0pt,colback=white,width=.6\textwidth]
      For the next two examples, we will use the angle sum formula for sine, which is
      \[\sin(\alpha+\beta)=\sin\alpha\cos\beta+\cos\alpha\sin\beta.\]
        \end{tcolorbox}}
\item For the function $y=\sin x,$ find the derivative, $y'.$
\begin{align*}
y'=\lim_{h\to 0}\frac{\sin (x+h)-\sin x}{h}&=\lim_{h\to 0}\frac{\sin x\cos h+\cos x\sin h-\sin x}{h}\\
&=\lim_{h\to 0}\frac{\sin x(\cos h-1)+\cos x\sin h}{h}\\
&=\left[\lim_{h\to 0}(\sin x)\left(\frac{\cos h-1}{h}\right)\right]\left[\lim_{h\to 0}(\cos x)\left(\frac{\sin h}{h}\right)\right]\\
&=(\sin x)\cdot 0+(\cos x)\cdot 1\\
&=\cos x,
\end{align*}
where we have used $\displaystyle\lim_{h\to 0}\frac{\sin h}{h}=1$ and $\displaystyle\lim_{h\to 0}\frac{\cos h-1}{h}=0$ from section (1.3).
\item Find $\dfrac{d}{dx}\tan x.$
\begin{align*}
\dfrac{d}{dx}\tan x=\displaystyle\lim_{h\to 0}\dfrac{\tan(x+h)-\tan x}{h}&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin(x+h)}{h\cos(x+h)}-\dfrac{\sin x}{h\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin(x+h)\cos x-\cos(x+h)\sin x}{h\cos(x+h)\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin[(x+h)-x]}{h\cos(x+h)\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left[\left(\dfrac{\sin h}{h}\right)\left(\dfrac{1}{\cos(x+h)\cos x}\right)\right]\\
&=\dfrac{1}{\cos^2(x)}=\sec^2 x.
\end{align*}
\end{enumerate}

\end{document}

The result:

enter image description here

I used

\usepackage[margin=2cm,showframe]{geometry}

in the example juts to have a visual guide of the page layout.

2

Another option is to use minipage environment as seen in the code

\documentclass[a4paper,11pt]{book}
\usepackage[T1]{fontenc}
\usepackage[utf8]{inputenc}
\usepackage{lmodern}
\usepackage{classicthesis}
\usepackage{hyperref}
\usepackage{graphicx}
\usepackage[english]{babel}
\usepackage{amsmath,mathtools}
\usepackage{amsfonts}
\usepackage{color}
\usepackage{url}
\usepackage{enumitem}
\usepackage{multicol}
\usepackage{tabu}
\usepackage{amsthm}
\usepackage{fourier-orns}
\usepackage{framed}
\usepackage{tcolorbox}
\usepackage[toc,page]{appendix}
\usepackage[all]{xy}

\begin{document}

\begin{enumerate}
\item For the function $y=x,$ find the derivative, $y'.$
\[y'=\lim_{h\to 0}\frac{(x+h)-x}{h}=\lim_{h\to 0}\frac{h}{h}=\lim_{h\to 0}1=1.\]
\item For the function $y=x^2,$ find the derivative, $y'.$
\begin{align*}
y'=\lim_{h\to 0}\frac{(x+h)^2-x^2}{h}&=\lim_{h\to 0}\frac{x^2+2xh+h^2-x^2}{h}\\
&=\lim_{h\to 0}\frac{2xh+h^2}{h}=\lim_{h\to 0}(2x+h)=2x.
\end{align*}

\begin{minipage}[c]{0.75\textwidth}
\begin{framed}
For the next two examples, we will use the angle sum formula for sine, which is
\[\sin(\alpha+\beta)=\sin\alpha \cos\beta+\cos\alpha \sin\beta.\]
\end{framed}
\end{minipage}


\item For the function $y=\sin x,$ find the derivative, $y'.$
\begin{align*}
y'=\lim_{h\to 0}\frac{\sin (x+h)-\sin x}{h}&=\lim_{h\to 0}\frac{\sin x\cos h+\cos x\sin h-\sin x}{h}\\
&=\lim_{h\to 0}\frac{\sin x(\cos h-1)+\cos x\sin h}{h}\\
&=\left[\lim_{h\to 0}(\sin x)\left(\frac{\cos h-1}{h}\right)\right]\left[\lim_{h\to 0}(\cos x)\left(\frac{\sin h}{h}\right)\right]\\
&=(\sin x)\cdot 0+(\cos x)\cdot 1\\
&=\cos x,
\end{align*}
where we have used $\displaystyle\lim_{h\to 0}\frac{\sin h}{h}=1$ and $\displaystyle\lim_{h\to 0}\frac{\cos h-1}{h}=0$ from section (1.3).
\item Find $\dfrac{d}{dx}\tan x.$
\begin{align*}
\dfrac{d}{dx}\tan x=\displaystyle\lim_{h\to 0}\dfrac{\tan(x+h)-\tan x}{h}&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin(x+h)}{h\cos(x+h)}-\dfrac{\sin x}{h\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin(x+h)\cos x-\cos(x+h)\sin x}{h\cos(x+h)\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left(\dfrac{\sin[(x+h)-x]}{h\cos(x+h)\cos x}\right)\\
&=\displaystyle\lim_{h\to 0}\left[\left(\dfrac{\sin h}{h}\right)\left(\dfrac{1}{\cos(x+h)\cos x}\right)\right]\\
&=\dfrac{1}{\cos^2(x)}=\sec^2 x.
\end{align*}
\end{enumerate}

\end{document}
1
  • This doesn't center the framed contents as was required. Jul 30 '15 at 19:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.